Effect of temperature on vacuum hot bulge forming of BT20 titanium alloy cylindrical workpiece - 王明伟 张立文 裴继斌 李辰辉 张凡云 (Transactions of Nonferrous Metals Society of China, 2007)
Temperature is one of the key parameters for BT20 titanium alloy cylindrical workpiece manufactured by vacuum hot bulge forming. A two-dimensional nonlinear thermo-mechanical coupled FE model was established. Numerical simulation of vacuum hot bulge forming process of titanium alloy cylindrical workpiece was carried out using FE analysis software MSC Marc. The effects of temperature on vacuum hot bulge forming of BT20 titanium alloy cylindrical workpiece were analyzed by numerical simulation. The simulated results show that the Y-direction displacement and the equivalent plastic strain of the workpiece increase with increasing bulge temperature. The residual stress decreases with increasing bulge temperature. The optimal temperature range of BT20 titanium alloy during vacuum hot bulge forming is 750-850 ℃. The corresponding experiments were carried out. The simulated results agreed well with the experimental results.